A semi‐active tuned liquid column damper for lateral vibration control of high‐rise structures: Theory and experimental verification. Issue 12 (8th October 2018) - Altay, Okyay; Klinkel, Sven
Summary: This paper presents a new type of semi‐active tuned liquid column damper (S‐TLCD) for the lateral vibration control of high‐rise civil engineering structures. Analogous to the passive tuned liquid column damper (TLCD), the S‐TLCD comprises a U‐shaped tank consisting of two vertical columns, which are arranged at a distance from each other and communicating through a horizontal passage. The tank is partially filled with a Newtonian fluid until the liquid reaches a certain level in the columns. In contrast to the passive TLCD, the S‐TLCD provides also mechanisms for a continuous adaptation of both its natural frequency and damping behaviour in real time. In the first part of the paper, the governing equations of the S‐TLCD are derived on the basis of the Bernoulli equation of a nonstationary incompressible liquid flow. The natural frequency of the S‐TLCD is revealed to depend on the scaled length of the liquid. The scaling amount of the liquid length is formulated in dependence of the cross‐sectional area ratios of the tank segments. The mathematical description of the S‐TLCD is concluded by providing the state‐space representation of a multi‐degree‐of‐freedom structure with several S‐TLCDs. In the second part of the paper, the derived natural frequency equation is verified, and the proof of concept of the S‐TLCD is shown by experimental investigations, which are performed on an S‐TLCD model utilizing a test structure and shaking table tests.